Oral Health Related Habits, Knowledge, and Frequency of Dental Floss use among Undergraduate Medical and Dental Students in a Public Health Sector University in Pakistan: A Comparative Study - Hina Shah, Sanaa Ahmed, Sadaf Talha, Sumbul Ayaz, Talha Bin Saeed, Marium Irshad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The current study aimed to evaluate oral health related habits, knowledge, and frequency of dental floss use among undergraduate medical and dental students. Methods: A cross-sectional study was undertaken at two institutes, Sindh Institute of Oral Health Sciences (SIOHS) and Sindh Medical College (SMC) of Jinnah Sindh Medical University (JSMU), Karachi, Pakistan, between March to May 2022. All undergraduate medical and dental students irrespective of gender, cast, creed, or socioeconomic status were eligible to partake in the study. The data on demographics including the age, gender, primary way of cleaning teeth, frequency of dental flossing, general oral health habits, assessment of knowledge of interdental cleaning aids etc. were recorded in a structured questionnaire. Results: The majority of the students acknowledged the importance of the role of students in promoting dental floss use among the community. Years of study in Bachelor of Dental Surgery (BDS) students was significantly associated with cleaning frequency (p < 0.0001) and primary cleaning method (p = 0.001). Interdental cleaning aid awareness, frequency of interdental cleaning, issues from not cleaning the interdental spaces, the role and use of dental floss were all significantly correlated with year of study among BDS students. Use of secondary methods was significantly associated with years of study among Bachelor of Medicine, Bachelor of Surgery (MBBS) students (p < 0.001). Conclusion: The present study concluded that years of study significantly correlated with the knowledge, awareness, and habits of dental students with respect to dental flossing. Keywords: dental hygiene, dental floss, interdental cleaning, oral health, dentist, medicine